Pengaruh Persentase Pemberian Pakan Berbeda Terhadap Laju Pertumbuhan Ikan Mas (Cyprinus Carpio L) Yang Dipelihara Dalam Bak Plastik - Brita Araino; Suriansyah Suriansyah; Kartika Bungas (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2014)
The objective of this research was to known percentage different of giving food on growth carp fish (Cyprinus carpio L.) cultured in the plastic basin, so that food conversion, growth rate relative, condition factor and survival rate carp fish (Cyprinus carpio) cultured can be optimal. The result research to showed value food conversion rate C (3,31) the higher by comparison with treatment A (1,79), and B (2,56), from the result analysis data food efficiency level treatment C more efficient with A and B. Growth rate Length relative fish test treatment A (0,852 %) ; B (1,040 %) ; C (1,199 %) and growth rate heavy and heavy relative treatment A (1,85 %) ; B (2,37 %) ; C (2,71 %), so that to know the growth the best is treatment C. Factor condition value rate in treatment A (2,3), B (2,1), and C (1,8). The growth length fish test in treatment A, B, and C more than dominant by comparison with growth heavy, because of the value factor condition smaller from 3. Survival rate carp fish of treatment A 86,6 %, B: 93,3 %, dan C : 100 %. Showed between treatment A, B, and C did not differ.